2014
DOI: 10.1155/2014/608608
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Parameters Related to the Etch Rate for a Dry Etch Process Using NF3/O2and SF6/O2

Abstract: The characteristics of the dry etching of SiN :H thin films for display devices using SF 6 /O 2 and NF 3 /O 2 were investigated using a dual-frequency capacitively coupled plasma reactive ion etching (CCP-RIE) system. The investigation was carried out by varying the RF power ratio (13.56 MHz/2 MHz), pressure, and gas flow ratio. For the SiN :H film, the etch rates obtained using NF 3 /O 2 were higher than those obtained using SF 6 /O 2 under various process conditions. The relationships between the etch rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This keeps the discharge stable and ensures collisionless sheaths as well as energetic vertical ion bombardment at the wafer. Similar discharge conditions are used for HAR dielectric plasma etching in CCPs [8][9][10][11][12][13][14][15]. The interest in this low-frequency and high voltage operation regime is the motivation of our studies.…”
Section: Introductionmentioning
confidence: 99%
“…This keeps the discharge stable and ensures collisionless sheaths as well as energetic vertical ion bombardment at the wafer. Similar discharge conditions are used for HAR dielectric plasma etching in CCPs [8][9][10][11][12][13][14][15]. The interest in this low-frequency and high voltage operation regime is the motivation of our studies.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the RF bias impedance of a fundamental frequency was the most useful parameter for detecting the end point of oxide etching. Oh et al [6] studied the parameters related to the etch rates of nitride in SF 6 /O 2 and NF 3 /O 2 gas. Using VI probe and OES, they introduced the parameter proportional to both the flux of the atomic fluorine and the etch rate.…”
Section: Introductionmentioning
confidence: 99%
“…While positive ions are accelerated towards the wafer by the sheath electric field and hit it vertically and continuously with high energies, electrons reach the substrate during the local sheath collapse at low energies and with a wide angular distribution [8]. The etch process is driven by high energy ions and reactive radicals [9][10][11][12][13][14][15][16], but the fluxes of positive ions and electrons must balance at each surface element of a dielectric wafer locally on time average, including the bottom and the sidewalls of trenches [8,17,18]. In the presence of a wide angular distribution, electrons cannot penetrate deeply into HAR trenches.…”
Section: Introductionmentioning
confidence: 99%